AXIOLOGICAL ASPECTS OF IMPLEMENTING THE SUSTAINABLE DEVELOPMENT GOALS IN THE CONTEXT OF DIGITALIZATION OF SOCIETY AND EDUCATION - Polishchuk, Oleksandr; Polishchuk, Olena (Proceedings of the National Aviation University Series Philosophy Cultural, 2025)
The modern world has undergone significant transformations that have led to numerous changes and a rethinking of human existence as a whole. In this context, education plays a crucial role, having shifted its value orientations in line with broader societal changes, as these values reflect the spirit of the era in which individuals live. Moreover, one of the key tasks of education is to prepare individuals for life in a digitalized environment within the framework of sustainable development goals. This demands new approaches to teaching and learning, as well as the cultivation of moral and ethical orientations that should accompany innovative processes. The aim and tasks. The aim of the article is to analyze the axiological dimensions of implementing the goals of sustainable development in the context of the digitalization of social being, with particular attention to the philosophy of education and relevant social and ethical theories. The tasks are to consider the basic principles of sustainable development and their axiological aspects; to investigate the role of education in the formation of values of sustainable development in the context of digital technologies; and to determine how the principles of sustainable development can be implemented in the educational process. Research methods include the methods of system analysis and synthesis, the Agile methodology, the synergistic method, forecasting, and the axiological approach. In their interaction, these methods contributed to achieving the stated objectives and fulfilling the overall aim of the study. Research results. The main principles of sustainable development and their axiological aspects were analyzed. It was established that the concept of sustainable development provides for a strategy for the development of society aimed at balancing the resolution of socio-economic issues with the preservation of the environment. This balance entails a shift in value orientations, as the technogenic nature of modern civilization has led to an ecological crisis. In response, contemporary education must foster critical thinking, a culture of responsibility, as well as adaptability and flexibility. As demonstrated by the study, education assumes a leading role in this process—not only by supporting the aforementioned competencies but also by instilling the values of sustainable development within the context of digital technologies. Discussion. It has been proven that digitalization processes have an impact on humans and society as a whole, changing them in accordance with the requirements of the environment and scientific discoveries. Sustainable development, in turn, includes not only environmental and economic aspects but also social values such as access to education, equality of opportunity, and inclusiveness. Conclusions. The conducted research provides grounds to assert that digitalization offers powerful tools for achieving the goals of sustainable development. However, without proper philosophical justification and an ethical framework, it may lead to opposite outcomes—sometimes unexpected, unpredictable, and even irreversible in their negative consequences. It is therefore essential that education, as one of the key social institutions, promotes values oriented toward harmony between humanity and nature, social justice, and the responsible use of technology. As the study demonstrates, education plays a crucial role in shaping the values of sustainable development.